Experiments with Pyrotechnic Compositions Based on a Mathematical Model: Part II Pyrotechnic Compositions Producing an Acoustic Effect with Optimum Properties - Jolanta Biegańska; Krzysztof Barański (Energies, 2022)
The article presents a method of evaluating pyrotechnic compositions producing an acoustic effect. The aforementioned pyrotechnic compositions are used in firecrackers to simulate a cannon shot. Optimum compositions that were selected (Part I Evaluation of the applicability of mathematical models in developing pyrotechnic compositions producing an acoustic effect) for testing were evaluated for their explosive and physicochemical properties. The following methods were used to evaluate suitability: measurement of the sound intensity level, the burning rate, and sensitivity to mechanical stimuli—friction and flash fire temperature. In addition, a test concerning the change in the properties of pyrotechnic compositions during storage was also performed.